THE ROLE OF THE IMAGES OF JAPAN AND ITS PREFECTURES IN THE ATTRACTIVENESS OF JAPAN AS A TOURIST DESTINATION - Alexandra S. Stegnienko; Irina S. Tikhotskaya; Shizuko Kato (Geography, Environment, Sustainability)
The article deals with the analysis of the tourist destination images of Japan and its prefectures and contains the results of the research carried out both based on examination of official Japanese statistics and tourist literature in Japanese, English and Russian and social polls in Russia and field studies in Japan. In this paper we present the results of the research conducted by the specially created for this work original method of tourist literature review that allowed us to select prefectures most rich in different tourist images and to develop a typology of Japanese prefectures. To present day the research of such kind is a unique one not only about Japan but on the whole as well.